Control interno, rotación del inventario y los gastos por deterioro - Torres Santana, María José (2024)
This thesis focuses on evaluating the interrelationship between internal control, inventory turnover and spoilage expenses in business environments. The importance of internal control is highlighted as a fundamental tool to save assets and improve operational efficiency. Regarding inventory rotation, we investigate how effective internal control can optimize this process, reducing storage costs and improving the ability to respond to market demand...